Community Engagement in the Fight Against COVID-19: Knowledge, Attitude, and Prevention Practices Among Dire Dawa Residents, Eastern Ethiopia - Umer, Abdurezak; Abdella, Kedir; Tekle, Yared; Debebe, Addisalem; Manyazewal, Tsegahun; Yuya, Mohammed; Mohammed, Hussen (Frontiers in Public Health, 2021)
Background: There is a global concern that coronavirus disease 2019 (COVID-19) cannot be addressed without the integration and active engagement of communities. We aimed to investigate the knowledge, attitude, and practices (KAP) of the residents in Eastern Ethiopia toward COVID-19. Method: A community-based cross-sectional study was conducted on May 1–30, 2020 among the residents of Dire Dawa, Eastern Ethiopia. Data were collected using a structured questionnaire on the awareness, knowledge, attitudes, and preventive practices toward COVID-19. We used random sampling to select the participants. Data was entered into the statistics and data (STATA) version for data cleaning and analysis. Binary logistic regression models with 95% CI were used to conduct bivariable [crude odds ratio (COR)] and multivariable [adjusted odds ratio (AOR)] analyses. Result: A total of 415 community residents responded to the questionnaire. Of those participants, 52.5% (95% CI 47.7–57) had adequate knowledge, 31.6% (95% CI 27–36) had favorable attitudes, and 49% (95% CI 45–50) had good practice toward the precautionary measures of COVID-19. Adequate knowledge had a significant association with urban residence (AOR = 5, 95% CI 3.1–8.4) and literacy (AOR = 3.1, 95% CI 1.5–6.7). Good preventions practices had a significant association with place of residence (AOR = 4.1, 95% CI 2.3–7.2), literacy (AOR = 2.9, 95% CI: 1,2–7.4), adequate knowledge (AOR = 3.5, 95% CI 2.3–5.8), and favorable attitude (AOR = 2.3, 95% CI 1.4–3.8) about the disease. Conclusion: The overall COVID-19-related KAP was inadequate in the majority of the residents of Dire Dawa that occupy irregular migration flows. These call for robust community-centered behavioral communication strategies that could bridge the gaps and help prevent and control COVID-19 and other future pandemics in their community.